Pengaruh Motivasi Kerja dan Gaya Kepemimpinan terhadap Kinerja Karyawan Inkoppabri - Tengku Airin Fedina (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This study aims to analyze the effect of work motivation and leadership style on employee performance at INKOPPABRI Karanggan, Gunung Putri, Bogor Regency. The background of this research is based on initial observations indicating decreased employee performance, such as lack of initiative, high absenteeism, and declining individual productivity. The research employed a quantitative approach using a survey method. The sample consisted of 40 respondents selected through a saturated sampling technique, where all members of the population were included. Data were collected via questionnaires and analyzed using multiple linear regression with SPSS version 26. The results revealed that both work motivation and leadership style had significant individual effects on employee performance. Simultaneously, these two independent variables showed a positive and significant influence on performance. Thus, work motivation and leadership style are key factors that must be considered by management in improving employee outcomes. The study provides practical implications for INKOPPABRI to develop strategies that enhance motivation and apply effective leadership styles to support overall organizational productivity.